2016
DOI: 10.17219/acem/31805
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-Dependent Apoptosis of Retinal Ganglion Cells During the Development of Diabetic Retinopathy

Abstract: Diabetic retinopathy constitutes the most frequent cause of vision loss in professionally active individuals. Progressive impairment of visual acuity results from massive fibrovascular proliferation involving the fundus of the eye, as well as from the apoptosis of the neuronal structures of the retina. The results of many clinical studies, both on experimental models and on human material, confirmed evident enhancement of this process in the course of diabetes. The programmed cell death of retinal ganglion cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
(44 reference statements)
2
20
0
Order By: Relevance
“…One group [33] found that this lack of arterial vasoconstrictor capacity was attributed to an alteration of nitric oxide production and bioavailability, whereas others [17] suggest that the overall reduced dilatory and constriction response could serve as an estimate of endothelial cell capacity to respond to a physiological stimulus. Furthermore, one study examining DM patients with varying severity of retinopathy demonstrated ganglion cell death with increasing severity of the retinopathy [35]. Our finding of more adverse endothelial markers in DM + CVD versus the other groups is in keeping with accepted pathophysiology [36, 37].…”
Section: Discussionsupporting
confidence: 85%
“…One group [33] found that this lack of arterial vasoconstrictor capacity was attributed to an alteration of nitric oxide production and bioavailability, whereas others [17] suggest that the overall reduced dilatory and constriction response could serve as an estimate of endothelial cell capacity to respond to a physiological stimulus. Furthermore, one study examining DM patients with varying severity of retinopathy demonstrated ganglion cell death with increasing severity of the retinopathy [35]. Our finding of more adverse endothelial markers in DM + CVD versus the other groups is in keeping with accepted pathophysiology [36, 37].…”
Section: Discussionsupporting
confidence: 85%
“…BCL family and caspases are prominent for the apoptosis. MCL-1 is one gene in BCL family, which inhibits caspase-3 and prohibits apoptosis [23]. In our study, we verified that hippocampal MCL-1 was down-regulated, while Caspase-3 was increased after diabetic modeling.…”
Section: Discussionsupporting
confidence: 71%
“…These pathways promote oxidative stress [Gurler et al, ; Kowluru and Chan, ], vascular dysfunction and the appearance of pro‐inflammatory cytokines, such tumor necrosis factor (TNF‐ α), interleukin‐6 (IL‐6), and interleukin‐1 beta (IL‐1β). Curiously, changes of glial cells are also often connected with early stages of the disease [Adamiec‐Mroczek et al, ]. Therefore, diabetic retinopathy can be considered a neurovascular disease.…”
Section: Diabetic Retinopathymentioning
confidence: 99%